Kant's philosophy and the momentum of modernity the metaphysics of fact determination - Roecklein, Robert J., 1960- (Lexington Books, 2019)
This book is a careful study of both Immanuel Kant's work and the context of that work in Early Modern Philosophy. Roecklein's chief concern is the philosophy of perception, which is manifest in Kant's doctrines of the transcendental aesthetic and the concept of phenomena.